# STEP II 2015 question 6 confusion

Watch
Announcements

Page 1 of 1

Go to first unread

Skip to page:

On the official solutions thread, the solution given for the 2nd part of question 6 is:

take y = pi - x.

=> dy = -dx. Substituting and noticing that sin x = sin(pi - x) gives that integral( xf(sin(x) ) = integral( (pi-x)f(sin x)).

We use this fact in evaluating I = integral(x/(1+sin x)). We get 2I = integral(pi/(1+sin x)). Hence I = pi/2.integral(1/(1+sin x)).

But if you make the substitution, you obtain integral(( pi -y) f(siny))dy. How can you just change the y's to x's???

take y = pi - x.

=> dy = -dx. Substituting and noticing that sin x = sin(pi - x) gives that integral( xf(sin(x) ) = integral( (pi-x)f(sin x)).

We use this fact in evaluating I = integral(x/(1+sin x)). We get 2I = integral(pi/(1+sin x)). Hence I = pi/2.integral(1/(1+sin x)).

But if you make the substitution, you obtain integral(( pi -y) f(siny))dy. How can you just change the y's to x's???

0

reply

Report

#2

(Original post by

On the official solutions thread, the solution given for the 2nd part of question 6 is:

take y = pi - x.

=> dy = -dx. Substituting and noticing that sin x = sin(pi - x) gives that integral( xf(sin(x) ) = integral( (pi-x)f(sin x)).

We use this fact in evaluating I = integral(x/(1+sin x)). We get 2I = integral(pi/(1+sin x)). Hence I = pi/2.integral(1/(1+sin x)).

But if you make the substitution, you obtain integral(( pi -y) f(siny))dy. How can you just change the y's to x's???

**Beddy**)On the official solutions thread, the solution given for the 2nd part of question 6 is:

take y = pi - x.

=> dy = -dx. Substituting and noticing that sin x = sin(pi - x) gives that integral( xf(sin(x) ) = integral( (pi-x)f(sin x)).

We use this fact in evaluating I = integral(x/(1+sin x)). We get 2I = integral(pi/(1+sin x)). Hence I = pi/2.integral(1/(1+sin x)).

But if you make the substitution, you obtain integral(( pi -y) f(siny))dy. How can you just change the y's to x's???

We have that

1

reply

Report

#3

**Beddy**)

On the official solutions thread, the solution given for the 2nd part of question 6 is:

take y = pi - x.

=> dy = -dx. Substituting and noticing that sin x = sin(pi - x) gives that integral( xf(sin(x) ) = integral( (pi-x)f(sin x)).

We use this fact in evaluating I = integral(x/(1+sin x)). We get 2I = integral(pi/(1+sin x)). Hence I = pi/2.integral(1/(1+sin x)).

But if you make the substitution, you obtain integral(( pi -y) f(siny))dy. How can you just change the y's to x's???

If you go into the Maths Exams subforum of the Maths subforum in the Maths, Science and Technology study help forum then you will see a STEP Prep thread 2016. You are likely to receive quicker answers if you post here.

I am not familiar with the question and typed mathematics like that is not the easiest to understand so please correct me if the below advice is not helpful.

Have they turned an integral of the form into one of the form ? If so they are completely the same integral. If you plotted graphs of z = g(y) and z = g(x) and found the areas between the curves and the y and x axes respectively you would get the same area.

1

reply

Report

#4

**Beddy**)

On the official solutions thread, the solution given for the 2nd part of question 6 is:

take y = pi - x.

=> dy = -dx. Substituting and noticing that sin x = sin(pi - x) gives that integral( xf(sin(x) ) = integral( (pi-x)f(sin x)).

We use this fact in evaluating I = integral(x/(1+sin x)). We get 2I = integral(pi/(1+sin x)). Hence I = pi/2.integral(1/(1+sin x)).

But if you make the substitution, you obtain integral(( pi -y) f(siny))dy. How can you just change the y's to x's???

0

reply

Report

#5

(Original post by

x.

**16Characters....**)x.

0

reply

Report

#6

(Original post by

This happens all the time. (posting at the same time)

**Zacken**)This happens all the time. (posting at the same time)

0

reply

Report

#7

(Original post by

Indeed it does :-) It's kind of coincidental that this thread was made today because earlier I couldn't be bothered with one of the differentiating trig functions examples my teacher was going through in class so I was playing around with changes of variable of the form on some trig integrals, though the only particularly interesting one was .

**16Characters....**)Indeed it does :-) It's kind of coincidental that this thread was made today because earlier I couldn't be bothered with one of the differentiating trig functions examples my teacher was going through in class so I was playing around with changes of variable of the form on some trig integrals, though the only particularly interesting one was .

0

reply

Report

#8

(Original post by

I find it fascinating that that works on a whole class of integrals: , the beauty of maths, eh?

**Zacken**)I find it fascinating that that works on a whole class of integrals: , the beauty of maths, eh?

0

reply

X

Page 1 of 1

Go to first unread

Skip to page:

### Quick Reply

Back

to top

to top